New constraints on ages of glasses proposed as reference materials for fission-track dating - Laurenzi, Marinella A.; Balestrieri, Maria Laura; Bigazzi, Giulio; Neto, Julio C. Hadler; Iunes, Pedro J.; Norelli, Pio; Oddone, Massimo; Osorio Araya, Ana Maria; Viramonte, Jose G. (Wiley-Blackwell, 2007)
New analyses have been performed in order to enhance the data-set on the independent ages of four glasses that have been proposed as reference materials for fission-track dating. The results are as follows. Moldavite - repeated (40)Ar/(39)Ar age determinations on samples from deposits from Bohemia and Moravia yielded an average of 14.34 +/- 0.08 Ma. This datum agrees with other recent determinations and is significantly younger than the (40)Ar/(39)Ar age of 15.21 +/- 0.15 Ma determined in the early 1980s. Macusanite (Peru) -four K-Ar ages ranging from 5.44 +/- 0.06 to 5.72 +/- 0.12 Ma have been published previously. New (40)Ar/(39)Ar ages gave an average of 5.12 +/- 0.04 Ma. Plateau fission-track ages determined using the IRMM-540 certified glass and U and Th thin films for neutron fluence measurements agree better with these new (40)Ar/(39)Ar ages than the previously published ages. Roccastrada glass (Italy) - a new (40)Ar/(39)Ar age, 2.45 +/- 0.04 Ma, is consistent with previous determinations. The Quiron obsidian (Argentina) is a recently discovered glass that has been proposed as an additional reference material for its high spontaneous track density (around 100 000 cm(-2)). Defects that might produce spurious tracks are virtually absent. An independent (40)Ar/(39)Ar age of 8.77 +/- 0.09 Ma was determined and is recommended for this glass. We believe that these materials, which will be distributed upon request to fission-track groups, will be very useful for testing system calibrations and experimental procedures.
Keywords: fission-track dating; (40)Ar/(39)Ar dating; natural glasses; age standards